2007
DOI: 10.1002/cncr.23169
|View full text |Cite
|
Sign up to set email alerts
|

Trends in childhood cancer incidence in the U.S. (1992–2004)

Abstract: BACKGROUND. The etiology of most pediatric neoplasms remains elusive. Examination of population-based incidence data provides insight regarding etiology among various demographic groups and may result in new hypotheses. The objective of the current study was to present updated information regarding childhood cancer incidence and trends in the U.S. overall and among demographic subgroups, including Asian/Pacific Islanders and Hispanics, for whom to the authors' knowledge trends have not been previously examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
425
3
25

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 578 publications
(471 citation statements)
references
References 33 publications
18
425
3
25
Order By: Relevance
“…The incidence rate for hepatoblastomas in Germany was similar to the rate in the Nordic countries for 1985-2006, 37 10 The increase did not stabilize during the study period. A nonsignificant increase of ∼1% annually was detected in an earlier European study.…”
Section: -2004mentioning
confidence: 55%
See 1 more Smart Citation
“…The incidence rate for hepatoblastomas in Germany was similar to the rate in the Nordic countries for 1985-2006, 37 10 The increase did not stabilize during the study period. A nonsignificant increase of ∼1% annually was detected in an earlier European study.…”
Section: -2004mentioning
confidence: 55%
“…The incidence rate for hepatoblastoma has been shown to have increased in the United States by 4.3% per year between 1992 and 2004 for children and adolescents 0 to 19 years old. 10 We have analyzed the embryonal tumors registered in the German Childhood Cancer Registry (GCCR) from 1991 to 2012 for incidence rates, trends, and survival probabilities. This is the first comprehensive study on pediatric embryonal tumors in Germany.…”
Section: What This Study Addsmentioning
confidence: 99%
“…However, the incidence was lower than in countries in North America [2,7] and Europe [17]. The rea- son for this worldwide variability in childhood cancer incidence is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Another possible reason for this increase is easy accessibility to hospital and treatment. Early studies in developed countries, based on data from the mid-to late-1970s, show increasing trends in incidence of childhood cancer [23,24]; however, more recent data from the United States (1992-2004) [2], Australia (1983-2006) [4], and Canada (1992-2006) [7] show a plateau in childhood cancer incidence. In this study, the incidence of most cancer subtypes showed an increasing trend; however, the incidence of 'other and unspecified malignant neoplasms' decreased annually (APC, -7.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation